Наукові підходи до класифікації туристично-рекреаційних ресурсів - Черчик, Лариса Миколаївна; Cherchyk, Larysa M. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті дано авторське визначення туристично-рекреацiйних ресурсів, розглянуто наукові підходи до їх типізації, запропоновано типізацію за низкою ознак. Деталізовано видове наповнення туристично-рекреацiйних ресурсів за компонентною структурою, яка передбачає виділення природних та суспільних ресурсів. The article given the author's definition of tourism and recreational resources reviewed scientific approaches to their characterization. On the basis of summarizing existing approaches suggested typing tourism and recreational resources on the following grounds: origin, specific use in activities, functions, component structures, administrative and spatial basis, the level of uniqueness, terms of use, accessibility, level of development, status. Detailed species filling tourism and recreational resources by component structures, which would provide natural and public tourism and recreational resources. Typing results are of practical importance, as they allow to justify the strategic plans of certain types of tourism and recreation, to justify and select the appropriate tools, rational uses, health inputs.
Scientific approach to the classification of tourism and recreational resources
Keywords: туристично-рекреацiйнi ресурси; туристично-рекреаційна сфера; природні ресурси та умови; суспільні ресурси; культурно-історичні ресурси; типізація; ознаки типізації; tourism and recreational resources; tourism and recreation; natural resources and conditions; public resources; cultural and historical resources; typing; typing characteristics